ESG strategies to deal with COVID-19 in a Brazilian public research company - Jesus, Igor Rosa Dias de; Nascimento, Petula Ponciano (Brazilian Journal of Operations & Production Management, 2021)
Goal: The paper aims to describe and discuss some practices and strategies that have been taken place in Embrapa Soils – a public research company that develops research in soil science – in order to deal with COVID-19 effects during the year of 2020. Design / Methodology / Approach: We have chosen the ESG approach – Environmental, Social and Governance – as a theoretical background to analyze the strategies and practice we bring up on this paper. Information we have used were collected from internal management systems. Results: Results show that the company have found many strategies to deal with COVID-19 in the three aspects of ESG. Positive results company have reached rely on leadership, processes adaptation and the strength of personal and professional connections among the employees. Limitations of the investigation: Strategies and practices we present are limited to the scope of one singular company. ESG is a methodology that we have used a posteriori to contextualize and analyze the situation. Practical implications: Learning and reinforcing the ESG approach have been an important tool for the company to think about itself beyond the boundaries of financial approaches. It has the potential to spread to other companies or public agencies that does not profit directly from its activities. Originality / Value: Sharing strategies and practices companies have used to deal with covid-19 is important as a benchmarking activity for other companies as well as it makes a remarkable narrative of management in uncertain times that can be useful for present and future generations.